The Causal Effects of Long-Term PM2.5 Exposure on COVID-19 in India - Yamada, Takahiro; Yamada, Hiroyuki; Mani, Muthukumara (World Bank, Washington, DC, 2021)
This study investigates the causal effects of long-term particulate matter 2.5 exposure on COVID-19 deaths, fatality rates, and cases in India by using an instrumental variables approach based on thermal inversion episodes. The estimation results indicate that a 1 percent increase in long-term exposure to particulate matter 2.5 leads to an increase in COVID-19 deaths by 5.7 percentage points and an increase in the COVID-19 fatality rate by 0.027 percentage point, but this exposure is not necessarily correlated with COVID-19 cases. People with underlying health conditions such as respiratory illness caused by exposure to air pollution might have a higher risk of death following SARS-CoV-2 infection. This finding might also apply to other countries where high levels of air pollution are a critical issue for development and public health.